HUBUNGAN ASUHAN KEPERAWATAN PELAYANAN BPJS DAN PELAYANAN UMUM TERHADAP KEPUASAN PASIEN - Bayu Imanuddin; Dwi Indah Normaningrum (Nusantara Hasana Berdikari, 2021)
Satisfaction is something that is used in role models as a determinant of the success of a service program that involves the patient's expectations of officers to provide good and fair services and does not discriminate between patients, both users of public and public health care should be treated equally. The purpose of this study was to determine a general description of the relationship between care of the BPJS care and public services to patient satisfaction. The method used in journal collection uses Google Scholer and Mendeley 2015-2020 issues. The literature review results on the relationship between nursing care services and public services to patient satisfaction. This is based on the results of patient satisfaction where the satisfaction of patients using BPJs is lower than that of general patients. This is evident from every journal available that shows that BPJS patient satisfaction is still low. And there are differences between BPJs patients and general patients regarding the quality provided in services such as discriminatory treatment, convoluted registration process, and feeling not served according to standard procedures.